1987
DOI: 10.1203/00006450-198708000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitochondrial Functions by Margosa Oil: Possible Implications in the Pathogenesis of Reye's Syndrome

Abstract: ABSTRACf. Margosa oil (MO), a fatty acid-rich extract of the seeds ofthe neem tree and a reported cause of Reye's syndrome, has been used in the induction of an experimental model of Reye's syndrome in rats. It has been reported that MO causes a decrease in in vivo mitochondrial enzyme activity similar to that seen in Reye's syndrome. We have attempted to uncover some of the biochemical mechanisms of MO's toxicity by examining its effect in vitro on isolated rat liver mitochondria . Male rat liver mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…There have been reports on the cytotoxicity of neem seed whose toxic principles include fatty acids, limonoids and unsaturated hydroxy aldehyde (Koga et al, 1987;Sinniah and Baskaran, 1981). However the toxicity of leaf and bark extracts is very low, especially when orally taken (Debelmas and Hache, 1976;Khattak et al, 1985;Singh et al, 1987).…”
Section: Discussionmentioning
confidence: 95%
“…There have been reports on the cytotoxicity of neem seed whose toxic principles include fatty acids, limonoids and unsaturated hydroxy aldehyde (Koga et al, 1987;Sinniah and Baskaran, 1981). However the toxicity of leaf and bark extracts is very low, especially when orally taken (Debelmas and Hache, 1976;Khattak et al, 1985;Singh et al, 1987).…”
Section: Discussionmentioning
confidence: 95%
“…101,102 Proliferation and hypertrophy of the endoplasmic reticulum and subsequent microvesicular steatosis have also been noted. 101,102 Proliferation and hypertrophy of the endoplasmic reticulum and subsequent microvesicular steatosis have also been noted.…”
Section: Margosa Oil (Neem)mentioning
confidence: 99%
“…The authors suggest that Kohomba oil causes changes in fatty acid metabolism which in turn interferes with mitochondrial respiration 4 . Onset of hepatic toxicity is quick as the oil reaches hepatocytes within 30 minutes of ingestion 3 .…”
Section: Case Reportmentioning
confidence: 99%
“…Studies on animal models have demonstrated both toxicity to the nervous system and pronounced fatty infiltration of the liver and proximal renal tubules with mitochondrial damage and cerebral oedema, occurring within 3 hours of administration of Kohomba oil, compatible with Reye syndrome 2,3,4 . The authors suggest that Kohomba oil causes changes in fatty acid metabolism which in turn interferes with mitochondrial respiration 4 .…”
Section: Case Reportmentioning
confidence: 99%